Association between anemia at three different time points and new-onset diabetes after kidney transplantation––a retrospective cohort study. (3rd April 2018) - Grossman, Alon; Ayalon-Dangur, Irit; Cooper, Lisa; Shohat, Tzippy; Rahamimov, Ruth; Mor, Eytan; Gafter-Gvili, Anat
ABSTRACT: Purpose : Anemia has been reported to be associated with diabetes, but the association between new-onset diabetes after transplantation (NODAT) and anemia has not been reported. Methods : Patients who underwent kidney transplantation and did not have diabetes prior to transplantation were included in this study. Hemoglobin levels and the prevalence of anemia (hemoglobin <12 g/dL in females and <13 g/dL in males) were evaluated at three time points (prior to transplantation, 6 months following transplantation or 1 month before the development of NODAT, 2 years following transplantation, or following the development of NODAT) and were compared between those who developed NODAT and those who did not. Variables associated with the development of anemia were compared between the two groups. Results : A total of 266 kidney transplant recipients were included, of which 71 (27%) developed NODAT during the time of the follow-up. Hemoglobin and hematocrit levels and the prevalence of anemia were similar in those with and without NODAT at all three time points evaluated. Ferritin levels, prior to transplantation and mean corpuscular volume (MCV) posttransplantation post-NODAT development, were slightly but significantly lower in those with NODAT, although both were within the normal range. Conclusions : Pretransplantation ferritin levels and posttransplantation post-NODAT development MCV are inversely associated with the development of NODAT in kidney transplants.